2020
DOI: 10.3389/fimmu.2020.01940
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Acrylamide Worsens the Inflammatory Responses in the Airways of Asthmatic Mice Through Agitation of Oxidative Stress in the Lungs

Abstract: Acrylamide is a toxic chemical substance produced when starch-rich foods are fried at high temperatures. Asthma is a chronic and complicated respiratory disease, of which genetic and environmental factors are the main triggers. Orally-received components may have an effect on asthma pathophysiology. The aim of this study was to investigate the role of AA as a stimulus in asthma. BALB/c mice were allocated into four groups as follows: two OVA-sensitized asthmatic groups, including one treated with AA by gavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Oxidative stress is a crucial factor in the pathophysiology of allergic asthma. Previous studies have provided a potential link between increased oxidative damage and the development, or worsening of allergic asthma [ 32 ]. In this study, exacerbated allergic asthma symptoms were found in the atopic march group compared with the OVA group, accompanied by the induction of pulmonary tissue oxidative stress, as indicated by decreased GSH and increased MDA levels ( Figure 7 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a crucial factor in the pathophysiology of allergic asthma. Previous studies have provided a potential link between increased oxidative damage and the development, or worsening of allergic asthma [ 32 ]. In this study, exacerbated allergic asthma symptoms were found in the atopic march group compared with the OVA group, accompanied by the induction of pulmonary tissue oxidative stress, as indicated by decreased GSH and increased MDA levels ( Figure 7 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin (IL)-4, IL-5, IL-9 and IL-13 are important cytokines that play key roles in type 2 immunity, and are usually involved in allergic diseases or during helminthic parasitic infections (8,9). Th2 cells and certain myeloid cells are considered the primary source of these type 2 cytokines (10,11); however, recent studies have reported that a rare subpopulation of innate lymphocytes are the predominant source (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a comparatively increased airway resistance at a lower versus higher MCh concentration would indicate a hyper-reactive airway response. The maximum tested MCh concentration was limited to 0.5 mg/mL because OVA-exposed mice exhibited severe dyspnea and could not tolerate higher concentrations found in preliminary studies [ 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%